1974
DOI: 10.1135/cccc19740154
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation catalysed by transition metal complexes coordinately bound to inorganic supports

Abstract: A series of Rh, Pd, and Pt complexes was prepared whose tert-phosphine, tert-amine, cyano or pyridine ligands are bonded directly or through alkylene chain to inorganic supports. The complexes were tested as catalysts for hydrosilylation of several alkene~ and of 1,3-butadiene by trichloro-, triethyl-, and triethoxysilane. In comparison with similar soluble complexes, supported catalysts were more selective and some could be reused. In several cases their effectivness was greater than that of the soluble catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
15
0
1
Order By: Relevance
“…[28a, 38] Shortly after, Capka and Hetflejs functionalized other inorganic materials with surface hydroxyl groups like galumina, molecular sieves (zeolites), and glass with several ligands. [39] Until now silica is the most popular matrix among the inorganic materials [28a, 40] because it is neutral and its surface properties [41] and possibilities to be modified [42,43] are well explored. Owing to the rigidity of the inorganic supports the donor groups were mainly bound through a flexible hydrocarbon chain (n !…”
Section: Historical Backgroundmentioning
confidence: 99%
“…[28a, 38] Shortly after, Capka and Hetflejs functionalized other inorganic materials with surface hydroxyl groups like galumina, molecular sieves (zeolites), and glass with several ligands. [39] Until now silica is the most popular matrix among the inorganic materials [28a, 40] because it is neutral and its surface properties [41] and possibilities to be modified [42,43] are well explored. Owing to the rigidity of the inorganic supports the donor groups were mainly bound through a flexible hydrocarbon chain (n !…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Speier's catalyst was not so effective when HSi(OEt) 3 was used. It was reported that the yield of decyltriethoxysilane was only 40% in the case of using H 2 PtCl 6 as catalyst [40]. We found that the hydrosilylation of 1-dodecene with HSi(OEt) 3 using 0.01 mol% H 2 PtCl 6 as catalyst afforded dodecyltriethoxysilane in 46% yield.…”
Section: Synthesis and Characterization Of Mcm-41-sh-rhmentioning
confidence: 85%
“…(20.24) Other research groups have adopted similar procedures for anchoring catalysts to silica (25)(26)(27) and to 'Y-alumina, glass, and molecular sieve zeolites. (27) …”
Section: Modification Of Preformed Polymersmentioning
confidence: 97%
“…For some applications, it has proven advantageous to remove unreacted surface silanol groups (through addition of trimethylchlorosilane, for example) prior to the use of these materials as catalysts. (20.24) Other research groups have adopted similar procedures for anchoring catalysts to silica (25)(26)(27) and to 'Y-alumina, glass, and molecular sieve zeolites. (27) …”
Section: Modification Of Preformed Polymersmentioning
confidence: 98%